2021
DOI: 10.1093/carcin/bgab107
|View full text |Cite
|
Sign up to set email alerts
|

Oral contraceptives and risk of breast cancer and ovarian cancer in women with a BRCA1 or BRCA2 mutation: a meta-analysis of observational studies

Abstract: It remains inconclusive whether the use of oral contraceptives (OCs) alters the risks of breast or ovarian cancer in women with a BRCA1 or BRCA2 mutation. We investigated the association between OC use and the risks of breast or ovarian cancer in this group by using a meta-analysis. PubMed and EMBASE were searched using keywords until February 2021 to identify relevant studies that evaluated the association between OC ever use and the risks of breast or ovarian cancer in women with a BRCA1 or BRCA2 mutation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…This theory would also explain the decreased risk of ovarian cancer associated with pregnancy and with COCP use, which results in reduced exposure to gonadotropins due to the steroid feedback on the pituitary. In the 2–3 years after menopause, gonadotropin levels are particularly high, such that concentrations of FSH and LH reach a peak of 10–20 times (50–100 mIU/ml) and 3–4 times (20–50 mIU/ml) the values recorded during the proliferative phase of the menstrual cycle, respectively, and after which there is a gradual but slight decline in both gonadotropins [ 15 , 16 ]. Thus, in support of the gonadotropin theory, the incidence of ovarian cancer climbs dramatically around the age at which most women reach menopause [ 45 ].…”
Section: Previously Proposed Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…This theory would also explain the decreased risk of ovarian cancer associated with pregnancy and with COCP use, which results in reduced exposure to gonadotropins due to the steroid feedback on the pituitary. In the 2–3 years after menopause, gonadotropin levels are particularly high, such that concentrations of FSH and LH reach a peak of 10–20 times (50–100 mIU/ml) and 3–4 times (20–50 mIU/ml) the values recorded during the proliferative phase of the menstrual cycle, respectively, and after which there is a gradual but slight decline in both gonadotropins [ 15 , 16 ]. Thus, in support of the gonadotropin theory, the incidence of ovarian cancer climbs dramatically around the age at which most women reach menopause [ 45 ].…”
Section: Previously Proposed Mechanismsmentioning
confidence: 99%
“…For example, most epidemiological studies have shown that oral contraception is associated with a 1.5–3.3-fold higher relative risk of cervical cancer by promoting human papilloma virus—DNA integration into the host genome, but only in users for > 5 years [ 13 ]. There is also a slight increase in the incidence of breast cancer after prolonged intake of COCPs [ 14 16 ]. Meanwhile, COCPs exposure is associated with reduced risk of endometrial, ovarian, lymphatic, colorectal and hematopoietic cancers that persists after discontinuation [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…BRCA1/2 mutation carriers also benefitted from the protective effects of COC use, which decreases the risk of ovarian cancer [ 97 ]. On the contrary, a new meta-analysis reported the elevated risk for breast cancer among long-term users (>5 years), while a protective effect for ovarian cancer was observed regardless of COC use [ 98 ]. Therefore, an elevation in BC risk cannot be ruled out.…”
Section: Brca1/2 Carriersmentioning
confidence: 99%
“…Oral contraceptives have proven preventive efficacy for ovarian cancer with a family history. However, it is controversial whether oral contraceptives increase the risk of breast cancer in BRCA1/2 mutation carriers ( 123 ).…”
Section: Regular Surveillance Prevention and Treatment For ...mentioning
confidence: 99%